Tribology performance of polyol-ester based TiO2, SiO2 and their hybrid nanolubricants - Hamisa, Abdul Hamid; Wan Hamzah, Wan Azmi; Mohd Farid, Ismail; Rosminazuin, Ab Rahim; Ali, Hafiz Muhammad (MDPI, 2023)
The tribology properties of TiO2/POE, SiO2/POE and TiO2-SiO2/POE nanolubricants were investigated for an automotive air-conditioning system with an electrically-driven compressor (EDC). A two-step preparation method was used in dispersing TiO2 and SiO2 nanoparticles into Polyol-ester (POE)-based lubricant at different volume concentrations of 0.01 to 0.1%. The coefficient of friction (COF) and wear scar diameter (WSD) were investigated using a Koehler four-ball tribo tester and microscopes. For the TiO2/POE, SiO2/POE and TiO2-SiO2/POE nanolubricants, respectively, the lowest COFs with maximum reduction were attained at 37.5%, 33.5% and 31.6% each at volume concentrations of 0.05%, 0.01% and 0.03%. The highest WSD reduction for the TiO2/POE and SiO2/POE mono nanolubricants were attained at 12.5% and 26.4%, respectively, at the same volume concentration of 0.01%. Meanwhile, the maximum reduction of WSD for the TiO2-SiO2/POE hybrid nanolubricant was reached at 12.4% at 0.03% volume concentration. As a conclusion, mono and hybrid nanolubricants with volume concentrations of less than 0.05% are suggested for use in air-conditioning systems with EDC because of their outstanding tribology performances. Further performance investigation of nanolubricants in the air-conditioning system is required to extend the present work.